Pathways to high performance: a qualitative comparative analysis of sport governing bodies - Winand, M.; Rihoux, B.; Robinson, L.; Zintz, T. (Nonprofit and Voluntary Sector Quarterly, 2013)
Nonprofit organizations are facing increasing pressure to become more performance oriented. Most research in this area has focused on the effects of a variety of independent variables on performance with little research focusing on combinations of factors that impact on performance. This article focuses on sport governing bodies from Belgium and measures and assesses their strategic goals and potential determinants of performance. Due to the small N-sample and the causal complexity inherent in this research, a crisp-set Qualitative Comparative Analysis (csQCA) was carried out which highlighted three pathways associated with high performance. High performance could be delivered by sport governing bodies that develop innovative activities for their members and are proactive in elite sport services; or that develop innovative activities and involve paid staff in decision-making processes; or that involve committed volunteers in decision-making processes and delegate activities they are not able to deliver themselves